Cisplatin-Associated Ototoxicity: A Review for the Health Professional - Jessica Paken; Cyril D. Govender; Mershen Pillay; Vikash Sewram (Journal of Toxicology)
Cisplatin is an effective drug used in the treatment of many cancers, yet its ototoxic potential places cancer patients, exposed to this drug, at risk of hearing loss, thus negatively impacting further on a patient’s quality of life. It is paramount for health care practitioners managing such patients to be aware of cisplatin’s ototoxic properties and the clinical signs to identify patients at risk of developing hearing loss. English peer-reviewed articles from January 1975 to July 2015 were assessed from PubMed, Science Direct, and Ebscohost. Seventy-nine articles and two books were identified for this review, using MeSH terms and keywords such as “ototoxicity”, “cisplatin”, “hearing loss”, and “ototoxicity monitoring”. This review provides an up-to-date overview of cisplatin-associated ototoxicity, namely, its clinical features, incidence rates, and molecular and cellular mechanisms and risk factors, to health care practitioners managing the patient with cancer, and highlights the need for a team-based approach to complement an audiological monitoring programme to mitigate any further loss in the quality of life of affected patients, as there is currently no otoprotective agent recommended routinely for the prevention of cisplatin-associated ototoxicity. It also sets the platform for effective dialogue towards policy formulation and strengthening of health systems in developing countries.